2011
DOI: 10.1017/s0142716411000191
|View full text |Cite
|
Sign up to set email alerts
|

Word frequency modulates morpheme-based reading in poor and skilled Italian readers

Abstract: A previous study reported that, similar to young and adult skilled readers, Italian developmental dyslexics read pseudowords made up of a root and a derivational suffix faster and more accurately than simple pseudowords. Unlike skilled readers, only dyslexic and reading-matched younger children benefited from morphological structure in reading words aloud. In this study, we show that word frequency affects the probability of morpheme-based reading, interacting with reading ability. Young skilled readers named … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
4
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(112 citation statements)
references
References 46 publications
9
95
4
4
Order By: Relevance
“…The pattern of results in the L1 beginning readers approached previous studies suggesting that decomposition of complex words (or even multi-morphemic non-words) into morphemic units supports reading ability in younger readers (Burani et al, 2008;Marcolini et al, 2011;Traficante et al, 2011). According to the above-mentioned literature, morpheme-based reading might allow children to read units smaller than the whole word, but bigger than the grapheme or the syllable (see, for instance, Angelelli et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The pattern of results in the L1 beginning readers approached previous studies suggesting that decomposition of complex words (or even multi-morphemic non-words) into morphemic units supports reading ability in younger readers (Burani et al, 2008;Marcolini et al, 2011;Traficante et al, 2011). According to the above-mentioned literature, morpheme-based reading might allow children to read units smaller than the whole word, but bigger than the grapheme or the syllable (see, for instance, Angelelli et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…According to these studies, words with a morphological structure (e.g., cass-iere, "cashier") were read faster than simple words (e.g., cammello, "camel") matched for length and frequency. Interestingly, morphological parsing speeded up reading times only in second graders and in children with dyslexia, but not in older skilled children (Burani, 2010;Marcolini et al, 2011;Angelelli, 2010;Angelelli, 2017). The authors concluded that children acquiring a transparent orthography such as Italian exploit morpheme-based reading and spelling to face difficulties in reading long unfamiliar words.…”
mentioning
confidence: 98%
“…These students read aloud pseudowords made up of a root and a derivational suffix (e.g. Finally, the presence of morphemes positively affected reading accuracy for pseudowords (Burani et al, 2008;Traficante et al, 2011), but not in the case of words, irrespective of word frequency or reading skill (Burani et al, 2008;Marcolini et al, 2011). dennosto; Burani et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, merely either whole word frequency or stem word frequency was taken into account instead of the effect of both. The previous researches had confirmed that compared with the whole word or stem familiarity, the effect of the comparative value for both of them (comparative familiarity) proved to be more effective (Marcolini et al 2011). Of the researches within China, only Zhang's (2014) employed participants' evaluation to obtain the familiarity index for the experiment materials and simultaneously took the effect of whole word familiarity and stem familiarity into account.…”
Section: Introductionmentioning
confidence: 99%